Reviving traditions in research on international market entry - Li, Tiger (JAI, 2003)
In contrast to the vibrant development in global market entry activities, extant research on the subject is running out of steam. For example, countertrade, a major form of entry mode, has grown to 15 per cent of the world trade but studies on the topic have dwindled to naught. The practice of gray market has expanded to include everything from batteries and cars to computers and mobile phones. However, research on gray market has become scarce. Research stagnancy does not limit to micro-marketing issues. The role of government in market entry has received little attention in spite of the active roles many governments, such as the Chinese and Indian governments, have played in creating a favorable environment to attract foreign direct investment and promote export. Written by a group of internationally renowned scholars, this volume of the "Advances in International Marketing" is devoted to bridge a knowledge gap between the practice of international market entry and the availability of research-based insights and principles for guiding that practice.
Keywords: International business enterprises.; Export marketing -- Research.; New products -- Research.; Competition, International.; Marketing research.; elektronické knihy; electronic books